2011
DOI: 10.1002/stem.708
|View full text |Cite
|
Sign up to set email alerts
|

Action at a Distance: Systemically Administered Adult Stem/Progenitor Cells (MSCs) Reduce Inflammatory Damage to the Cornea Without Engraftment and Primarily by Secretion of TNF-α Stimulated Gene/Protein 6

Abstract: Previous reports demonstrated that the deleterious effects of chemical injury to the cornea were ameliorated by local or systemic administration of adult stem/progenitor cells from bone marrow referred to as mesenchymal stem or stromal cells (MSCs). However, the mechanisms for the beneficial effects of MSCs on the injured cornea were not clarified. Herein, we demonstrated that human MSCs (hMSCs) were effective in reducing corneal opacity and inflammation without engraftment after either intraperitoneal (i.p.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
193
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(207 citation statements)
references
References 40 publications
11
193
3
Order By: Relevance
“…Two recent reports have confirmed this TSG-6-dependent, but engraftmentindependent, action at a distance of grafted MSCs, in mice with both EAE (Fisher-Shoval et al, 2012) and ethanol-induced corneal inflammation (Roddy et al, 2011) (Table 3).…”
Section: Signaling At a Distance (Endocrine)mentioning
confidence: 61%
See 1 more Smart Citation
“…Two recent reports have confirmed this TSG-6-dependent, but engraftmentindependent, action at a distance of grafted MSCs, in mice with both EAE (Fisher-Shoval et al, 2012) and ethanol-induced corneal inflammation (Roddy et al, 2011) (Table 3).…”
Section: Signaling At a Distance (Endocrine)mentioning
confidence: 61%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%
“…TSG-6 is a 35-kDa protein that is secreted in response to TNF-a or IL-1b and is natural modulator of inflammation. 27,28 We, and others, have shown that hMSCs suppresses excessive sterile inflammation thereby ameliorating lung injury, 5 myocardial infarction, 29 corneal injury 30 or peritonitis, 26 in part due to hMSCs activation and secretion of TSG-6. Recently, Lee et al, 7 have proposed TSG-6 mRNA levels as a biomarker to predict in vivo efficacy in suppressing inflammation of different donor-derived hMSCs prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, observations by our group and others identified TSG-6 as being responsible for the beneficial effects of MSCs in the treatment of disease models of the heart (4), cornea (5,19,32), brain (33), lung (34), and pancreas (35). TSG-6 exerts its antiinflammatory actions through multiple mechanisms, one of which is the modulation of myeloid cells into a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%